Stair climbing – An insight and comparison between women with and without joint hypermobility: A descriptive study. Issue 1 (February 2015) - Luder, Gere; Schmid, Stefan; Stettler, Matthias; Mueller Mebes, Christine; Stutz, Ursula; Ziswiler, Hans-Rudolf; Radlinger, Lorenz
Abstract Generalized joint hypermobility (GJH) is a frequent entity in rheumatology with higher prevalence among women. It is associated with chronic widespread pain, joint dislocations, arthralgia, fibromyalgia and early osteoarthritis. Stair climbing is an important functional task and can induce symptoms in hypermobile persons. The aim of this study was to compare ground reaction forces (GRF) and muscle activity during stair climbing in women with and without GJH. A cross-sectional study of 67 women with normal mobility and 128 hypermobile women was performed. The hypermobile women were further divided into 56 symptomatic and 47 asymptomatic. GRFs were measured by force plates embedded in a six step staircase, as well as surface electromyography (EMG) of six leg muscles. Parameters derived from GRF and EMG were compared between groups using t-test and ANOVA. For GRF no significant differences were found. EMG showed lower activity for the quadriceps during ascent and lower activity for hamstrings and quadriceps during descent in hypermobile women. For symptomatic hypermobile women these differences were even more accentuated. The differences in EMG may point towards an altered movement pattern during stair climbing, aimed at avoiding high muscle activation. However, differences were small, since stair climbing seems to be not demanding.